1997
DOI: 10.1016/s0735-1097(96)00532-3
|View full text |Cite
|
Sign up to set email alerts
|

The Prehospital Electrocardiogram in Acute Myocardial Infarction: Is Its Full Potential Being Realized? fn1fn1The National Registry of Myocardial Infarction 2 is supported by Genentech, Inc., South San Francisco, California.

Abstract: The prehospital ECG is infrequently utilized for diagnosing myocardial infarction, and among patients with a prehospital ECG, is associated with a longer time from symptom onset to hospital arrival. Despite these shortcomings, the prehospital ECG is a test that may potentially influence the management of patients with acute myocardial infarction through wider, faster in-hospital utilization of reperfusion strategies and greater usage of invasive procedures, factors that may possibly reduce shortterm mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(69 citation statements)
references
References 29 publications
1
63
0
5
Order By: Relevance
“…The low number of NSTEMI patients with pECGs is similar to the number of STEMI patients that had a pECG when first initiated. 20 This may be reflective of the novelty of this procedure in NSTEMI patients and the need for additional education of the public as well as education and training of prehospital providers. This idea is reinforced in the stratifiedanalysis comparing patients within the lower pECG and higher pECG centers.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of NSTEMI patients with pECGs is similar to the number of STEMI patients that had a pECG when first initiated. 20 This may be reflective of the novelty of this procedure in NSTEMI patients and the need for additional education of the public as well as education and training of prehospital providers. This idea is reinforced in the stratifiedanalysis comparing patients within the lower pECG and higher pECG centers.…”
Section: Discussionmentioning
confidence: 99%
“…The use of onsite ECGs should be the standard of pre-hospital acute MI care to further reduce total ischemic times. [32][33][34][35][36] This can be done safely and accurately.…”
Section: Discussionmentioning
confidence: 99%
“…23 A study by Canto et al using a database of 275 000 from the National Registry of Myocardial Infarction showed that only 5% of patients receive field electrocardiography. 27 Where ambulance service paramedics do use 12 lead electrocardiography to assist with early diagnosis of AMI, they achieve this in one of two ways. Either the 12 lead electrocardiogram (ECG) is transmitted to a doctor who makes a diagnosis (and may communicate this diagnosis back to the ambulance crew), or alternatively, ambulance paramedics are trained to interpret the ECG themselves.…”
Section: Lead Electrocardiographymentioning
confidence: 99%
“…28 The successful interpretation of the 12 lead electrocardiography by trained paramedics has now been documented in several studies. [22][23][24][25][26][27][28][29][30][31][32][33] For example, a 5 year study in Canada showed that paramedics can accurately identify patients who would have the greatest likelihood of benefiting from early, aggressive thrombolytic therapy. 33 Moreover, a study in the UK compared paramedics and cardiologists; 22 paramedics received two days intensive training in interpretation of a 12 lead ECG followed by consolidation in the field, after which time it was demonstrated that there was no significant difference between the two groups in recognition of ST segment elevation.…”
Section: Lead Electrocardiographymentioning
confidence: 99%
See 1 more Smart Citation